Neural activity in mediodorsal nucleus of thalamus in rats performing a working memory task - Han, Jihyero; Lee, Ji H.; Kim, Min J.; Jung, Min W. (Frontiers in Neural Circuits, 2013)
The neural circuit consisting of mediodorsal nucleus (MDN) of thalamus and prefrontal cortex has been implicated in working memory. In order to investigate whether and how the rodent MDN processes working memory-related signals, we recorded activity of single neurons from the MDN in rats performing a delayed spatial alternation task. The MDN conveyed significant neural signals for the animal's previously chosen goal (retrospective information) in the early delay period, but the signals deteriorated gradually over time so that they became weak toward the end of the delay period. Neural signals for the animal's upcoming goal choice (prospective information) were even weaker than those for the previously chosen goal. These results are in contrast to the finding in monkeys that both MDN and prefrontal cortex persistently maintain task-related neural signals throughout delay period. Our results do not support sustained MDN-prefrontal cortex interactions as a general mechanism for mediating working memory across different behavioral tasks and/or animal species.